Vacuum-assisted foetal delivery device to remove a rectal foreign body - A novel application of the Ventouse method - Basilie Teoh; Raaj Chandra; Jacob McCormick; Ran Li (Journal of Surgery and Surgical Research - Peertechz Publications, 2019)
Rectal foreign bodies (RFBs) are an unusual emergency presentation readily confirmed via clinical examination and imaging, which must be quickly removed due to the risk of rectal wall tissue damage leading to perforation and subsequent peritonitis. Several non-operative methods are described in the literature to retrieve RFBs, however removal can be especially difficult if they not easily graspable, for example a ball-like object. We present the case of a spherical RFB successfully extracted using a vacuum-assisted delivery device.